Effect of TDP2 on the Level of TOP2-DNA Complexes and SUMOylated TOP2-DNA Complexes - Lee, Ka Cheong (Int J Mol Sci, 2018)
DNA topoisomerase II (TOP2) activity involves a normally transient double-strand break intermediate in which the enzyme is coupled to DNA via a 5′-phosphotyrosyl bond. However, etoposide and other topoisomerase drugs poison the enzyme by stabilising this enzyme-bridged break, resulting in the accumulation of TOP2-DNA covalent complexes with cytotoxic consequences. The phosphotyrosyl diesterase TDP2 appears to be required for efficient repair of this unusual type of DNA damage and can remove 5′-tyrosine adducts from a double-stranded oligonucleotide substrate. Here, we adapt the trapped in agarose DNA immunostaining (TARDIS) assay to investigate the role of TDP2 in the removal of TOP2-DNA complexes in vitro and in cells. We report that TDP2 alone does not remove TOP2-DNA complexes from genomic DNA in vitro and that depletion of TDP2 in cells does not slow the removal of TOP2-DNA complexes. Thus, if TDP2 is involved in repairing TOP2 adducts, there must be one or more prior steps in which the protein-DNA complex is processed before TDP2 removes the remaining 5′ tyrosine DNA adducts. While this is partly achieved through the degradation of TOP2 adducts by the proteasome, a proteasome-independent mechanism has also been described involving the SUMOylation of TOP2 by the ZATT E3 SUMO ligase. The TARDIS assay was also adapted to measure the effect of TDP2 knockdown on levels of SUMOylated TOP2-DNA complexes, which together with levels of double strand breaks were unaffected in K562 cells following etoposide exposure and proteasomal inhibition.